Recognizing Texas Women in Time and Space: A Qualitative GIS Inquiry into Historical Markers. - Ansah, Hilary; Lu, Yongmei; Choi, Yusik (Geographical Review)
Historical markers offer important insights into the portrayal of place, social dynamics, and untold narratives within various landscapes. The vast collection of over 195,000 historical markers scattered throughout the United States provide a wealth of data that can shed light on distinctive representation patterns and narratives associated with different individuals and events. Yet, only a few studies examined historical markers as a valuable data source. The goal of this study is to investigate how Texas women are commemorated through historical markers and to uncover the spatial and temporal patterns and contexts associated with these commemorations. We utilize qualitative GIS method and a suite of corpus linguistics techniques to analyze the spatial, temporal, and thematic patterns of the historical markers in Texas that are dedicated to women. Our findings address the existing gender imbalance and shed light on the underrepresentation of women in Texas' historical narratives.